SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN LAPTOP MENGGUNAKAN METODE FUZZY DATABASE MODEL TAHANI BERBASIS WEB - Umar, Fahmy; Widjianto, Widjianto; Widarti, Dinny Wahyu (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2015)
Laptop is a product needed by the community in various fields, either education or business in general. The problem arises when someone wants to buy a laptop. what laptop type is appropriate for the person and how to determine the recommendations will be given. Decision support system is capable of providing a solution to the problem of selecting a laptop. With Tahani model Fuzzy Database, decision support system is capable of processing unstructured data and assisting in the decisions required in this study. This research resulted in the information in the form of a laptop recommendation in accordance with the criteria desired by the user. Using a blackbox testing and field trials with a questionnaire, systems and applications in this research could work well and provide benefits to users. Keywords : Sistem Pendukung Keputusan, Notebook, Fuzzy Tahani.